Histological evaluation of the lesion induced by inoculation of Leishmania mexicana in the cheek pouch of the hamster - Arruda, Maria Sueli Parreira de [UNESP]; Nogueira, Maria Esther Salles; Bordon, Ana Paula [UNESP] (Sociedade Brasileira de Medicina Tropical - SBMT, 2002)
No presente estudo, investigamos o papel da resposta imune na morfologia do granuloma leishmaniótico induzido na bolsa jugal do hamster, um local imunologicamente privilegiado, após inoculação de 3x10(5) Leishmania mexicana. Os animais foram avaliados histológica e imunologicamente até os 120 dias da inoculação. Independente da época do sacrifício, os animais foram sempre não reatores ao teste do coxim plantar. Histologicamente, a inoculação de Leishmania mexicana na bolsa jugal resultou na formação de abcesso que evoluiu para reação granulomatosa rica em formas amastigotas e, posteriormente, para resolução. Esses resultados sugerem que o desenvolvimento da resposta imune não é preponderante no controle da infecção induzida pela Leishmania mexicana inoculada subcutaneamente na bolsa jugal do hamster. Sugerem ainda que os macrófagos que compõe os granulomas leishmanióticos são capazes de eliminar esse parasita, independente da presença de resposta imune avaliável pelo teste do coxim plantar.

We have studied the role of the immune response in the morphology of the leishmaniotic granuloma induced in the cheek pouch of hamsters, an immunologically privileged site, after inoculation of 3 x 10(5) Leishmania mexicana. Animals were histologically and immunologically evaluated until 120 days after inoculation. Independent of the time of sacrifice, the animals were always non-reactors to the footpad test (FPT). At histology, the introduction of L. mexicana in the cheek pouch leads to an abscess that evolves to a granulomatous reaction rich in amastigote forms, and later it leads to resolution, even in the absence of immune response detectable by FPT. Our results demonstrate that the development of immune response is not preponderant for the control of infection induced by L. mexicana inoculated subcutaneously in the cheek pouch of the hamster. It also suggests that the macrophages present in the leishmaniotic granuloma are capable of eliminating this parasite, even in the absence of immune response evaluated by FPT.
Avaliação histológica da lesão induzida pela inoculação de Leishmania mexicana na bolsa jugal do hamster
Keywords: Bolsa jugal do hamster; Leishmaniose experimental; Leishmania mexicana; Cheek pouch; Experimental leishmaniasis; Leishmania mexicana